Investigation of the MALDI process used to characterize self-assembled monolayers of alkanethiolates on gold - Ha, Tae Kyung (Langmuir : the ACS journal of surfaces and colloids, 2009)
In this work, we investigated the surface processes involved in matrix-assisted laser desorption/ionization (MALDI) mass spectrometry (MS), which produce intact characteristic ions, typically in disulfide form, from self-assembled monolayers (SAMs) of alkanethiolates on gold. For the study, SAMs decorated with peptides and a THAP matrix were employed. Using two-laser MS, it was previously found that irradiation with a UV laser gave rise to the direct desorption of SAM molecules from alkanethiol SAMs on gold, producing disulfide species in vacuum. However, a closer examination of this study suggests that the MALDI process in which the matrix is used may not be the case. Instead, the results indicate that the treatment of the matrix solution is responsible for the characteristic ion formation in MALDI MS. We propose that the matrix solution dissolves alkanethiolate molecules from SAMs, leading to the generation of characteristic disulfide species in the solution. The disulfides are then cocrystallized with matrix molecules and subsequently detected by MALDI MS. Because MALDI MS is a powerful tool for biopolymers with high molecular weights, it has been successfully applied to SAMs presenting large biomolecules. This understanding of the MALDI process in the surface MS of alkanethiol SAMs on gold may allow advances in the biomolecular application of SAMs in combination with mass spectrometric analysis